2014
DOI: 10.3892/mmr.2014.1935
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone induces endoplasmic reticulum stress in PC12 cells

Abstract: Naloxone is an opioid inverse agonist used in the treatment of opiate overdose, with well known pharmacology. In the present study, we determined the effects of naloxone on the unfolded protein response (UPR) in PC12 cells. Data from a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay indicated that naloxone may accelerate PC12 cell apoptosis in a dose-dependent manner. We also demonstrated that naloxone upregulated gene expression of endoplasmic reticulum (ER) chaperones, including bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Naloxone, an opioid receptor antagonist, could upregulate gene expression of ER chaperones in PC12 cells, including BiP, calnexin, ER protein 29 and protein disulfide isomerase, and ER stress sensors, including ATF6, IRE1, and PERK. In addition, naloxone could also induce typical ER stress phenomena, including ART6 proteolytic cleavage, eIF2α phosphorylation and XBP1 mRNA splicing ( Seo et al, 2014 ). Jian et al (2014) found that the retrieval of morphine memory was associated with the dephosphorylation of eIF2α expression in basolateral amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…Naloxone, an opioid receptor antagonist, could upregulate gene expression of ER chaperones in PC12 cells, including BiP, calnexin, ER protein 29 and protein disulfide isomerase, and ER stress sensors, including ATF6, IRE1, and PERK. In addition, naloxone could also induce typical ER stress phenomena, including ART6 proteolytic cleavage, eIF2α phosphorylation and XBP1 mRNA splicing ( Seo et al, 2014 ). Jian et al (2014) found that the retrieval of morphine memory was associated with the dephosphorylation of eIF2α expression in basolateral amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Endoplasmic reticulum protein 29 is inducible under cellular stress, such as thapsigargin-or tunicamycin-induced ER stress in rat hepatoma cells 2 or naloxone-induced ER stress in PC12 cells. 6 Structural studies have revealed that ERp29 contains a N-terminal thioredoxin domain that resembles protein disulfide isomerase (PDI), 7 and may play a role in protein folding. Furthermore, ERp29 has been shown to interact with and enhance the function of other ER chaperones, such as GRP94, GRP78, ERp72, and calnexin.…”
mentioning
confidence: 99%
“…In addition, ER stress activation was found in the peripheral nervous system of diabetic nephropathy rats [24]. Moreover, a few recent studies have reported that ER stress has a role in morphine analgesia and tolerance mechanisms [27,28]. It has also been found that PERK/eIF2a ER stress pathway activation increased after tolerance in the spinal cord [28].…”
Section: Discussionmentioning
confidence: 96%